Progress and performance evaluation of BeiDou global navigation satellite system: Data analysis based on BDS-3 demonstration system - Yang, Yuanxi; Xu, Yangyin; Li, Jinlong; Yang, Cheng (Science China. Earth sciences, 2018)
The first two Medium Earth Orbit (MEO) satellites of the third generation of BeiDou satellite navigation System (BDS-3) were successfully launched on November 5, 2017. This historical launch starts the new era of the global navigation satellite system of BeiDou. Before the first two satellites of BDS-3, a demonstration system for BDS-3 with five satellites, including two Inclined Geosynchronous Orbit satellites (IGSO) and three MEO satellites, was established between 2015 and 2016 for testing the new payloads, new designed signals and new techniques. In the demonstration system, the new S frequency signal and satellite hydrogen clock as well as inter-satellite link (ISL) based on Ka-band signals with time-division multiple addresses (TDMA) were tested. This paper mainly analyzes the performances of the demonstration system, including the signalto- noise ratios, pseudorange errors and the multipath errors of the civilian signals of BDS-3. The qualities of signals in space, time synchronization and timing precision were tested as well. Most of the performances were compared with those of the regional BeiDou satellite navigation system (BDS-2). At last, the performances of positioning, navigation and timing (PNT) of the future BeiDou global system (BDS-3) were evaluated based on the signal quality of the present demonstration satellite system.